The Use Of Audio Visual Media In Learning To Write Advertisement Texts Class Viii Students - Nurafifah, Siti; Widiastuti, Widiastuti (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to determine the use of audio-visual media in teaching students to write advertisement texts in poster form for class VIII-6 students at SMPN 87 Jakarta during the 2018/2019 academic year. Methodology: This study used a descriptive qualitative method. Data collection instruments included observation sheets, interview guidelines, assignments, and documentation. The data were analyzed using test and non-test analysis with data recap tables. The media used was a motion graphic video titled "Bahaya Rokok." Main Findings: The first writing test without audio-visual media showed an average score of 7.1 with only 2 students reaching the passing score. In contrast, after implementing the motion graphic video in the second test, the average score increased to 8.6 with 33 students reaching the minimum passing score. The use of the video significantly improved students’ writing skills in advertisement texts. Novelty/Originality of this study: This study introduces the use of motion graphic video as an innovative tool in language instruction, particularly in teaching advertisement texts. It offers empirical insight into how media can enhance writing engagement and outcomes, especially for texts with persuasive purposes in junior high school settings.